2009
DOI: 10.1016/j.aap.2008.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Markov switching negative binomial models: An application to vehicle accident frequencies

Abstract: In this paper, two-state Markov switching models are proposed to study accident frequencies. These models assume that there are two unobserved states of roadway safety, and that roadway entities (roadway segments) can switch between these states over time. The states are distinct, in the sense that in the different states accident frequencies are generated by separate counting processes (by separate Poisson or negative binomial processes). To demonstrate the applicability of the approach presented herein, two-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 164 publications
(68 citation statements)
references
References 22 publications
2
64
0
Order By: Relevance
“…This approach provided useful information on features of the population. A similar approach by Malyshkina et al (2009) also demonstrated the usefulness of two-state Markov switching models in terms of goodness-of-fit and the capability of capturing unobserved heterogeneity. The finite mixture regression model rests on the assumption that there are a finite number of unobservable categories of observations and the heterogeneity arises from different values of regression coefficients caused by missing variables (Frühwirth-Schnatter, 2006).…”
Section: Introductionmentioning
confidence: 90%
“…This approach provided useful information on features of the population. A similar approach by Malyshkina et al (2009) also demonstrated the usefulness of two-state Markov switching models in terms of goodness-of-fit and the capability of capturing unobserved heterogeneity. The finite mixture regression model rests on the assumption that there are a finite number of unobservable categories of observations and the heterogeneity arises from different values of regression coefficients caused by missing variables (Frühwirth-Schnatter, 2006).…”
Section: Introductionmentioning
confidence: 90%
“…Recently, the problems associated with the long-term mean equal to zero have been discussed by other researchers (see, e.g., Malyshkina et al, 2009). As an alternative, have proposed a zero-sate Markov switching countdata model for circumventing the problem of having the long-term mean equal to zero.…”
mentioning
confidence: 99%
“…Two-state Markov switching count-data models of accident frequencies were first presented in Malyshkina et al (2009). Following that paper, we note that, although there are several major differences between Malyshkina et al (2009) and this study, many ideas and statistical estimation methods developed in Malyshkina et al (2009) apply in this study as well.…”
Section: Model Specificationmentioning
confidence: 95%